2005
DOI: 10.1021/np040203r
|View full text |Cite
|
Sign up to set email alerts
|

Antineoplastic Agents. 534. Isolation and Structure of Sansevistatins 1 and 2 from the African Sansevieria ehrenbergii,1

Abstract: Using bioactivity-directed isolation procedures, three new spirostanol saponins designated sansevierin A (1), sansevistatin 1 (2), and sansevistatin 2 (3) were isolated (10(-5) % yield) from the CH3OH-CH2Cl2 extract of Sansevieria ehrenbergii, accompanied by three known steroidal saponins (4-6). The structures were determined on the basis of chemical methods and spectroscopic analysis, especially 1D and 2D NMR experiments. Each of the saponins was evaluated against the P388 lymphocytic leukemia cell line and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…The location of 7-OH also could be confirmed by the HMBC correlations of H-6/C-7, H-7/C-5, and H-7/C-9. The a-orientation of 7-hydroxyl group could be determined by the resonance of C-7 (d 64.6) (Pettit et al, 2005), while the signal for C-7 would be at d 72.6 of the 7b-isomer (Blunden et al, 1990). Furthermore, in the 13 C NMR spectrum of 4, the signals of C-9 (d 42.7) and C-14 (d 49.9), were up-field of corresponding signals in the spectrum of diosgenin (d 50.1 and d 56.5, respectively) (Agrawal et al, 1985;Chen et al, 1995) due to the c-gauche interactions.…”
Section: Resultsmentioning
confidence: 99%
“…The location of 7-OH also could be confirmed by the HMBC correlations of H-6/C-7, H-7/C-5, and H-7/C-9. The a-orientation of 7-hydroxyl group could be determined by the resonance of C-7 (d 64.6) (Pettit et al, 2005), while the signal for C-7 would be at d 72.6 of the 7b-isomer (Blunden et al, 1990). Furthermore, in the 13 C NMR spectrum of 4, the signals of C-9 (d 42.7) and C-14 (d 49.9), were up-field of corresponding signals in the spectrum of diosgenin (d 50.1 and d 56.5, respectively) (Agrawal et al, 1985;Chen et al, 1995) due to the c-gauche interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the furostanol saponins were converted to the spirostanol saponins by enzymatic hydrolysis with β-glucosidase. Finally, the obtained spirostanol saponins were fractionated on silica gel column chromatography and further purified repeatedly by semipreparative RP-HPLC to give 9 spirostanol saponins (1-9) and 7 mixtures of 25R and 25S isomers (10)(11)(12)(13)(14)(15)(16), and their structures were elucidated based on NMR and MS spectra (l " Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous investigations suggested that spirostanol saponins had stronger activity than the corresponding furostanol saponins on platelet aggregation [9,10]. To obtain the potentially bioactive compounds, we converted the furostanol saponins of TFG seeds to the spirostanol saponins by enzymatic hydrolysis with β-glucosidase, and finally nine spirostanol saponins (1-9) along with seven mixtures of spirostanol saponin 25R and 25S isomers (10)(11)(12)(13)(14)(15)(16) were rapidly isolated, and their structures were elucidated based on NMR and MS spectra. Among them, 1-4, 6, 8, 9, 11b, 12a, 13b, 14a, and 14b were new spirostanol saponins.…”
mentioning
confidence: 99%
“…For example, the plant is used to treat wounds, for tying, construction, and washing utensils in Kenya (Khalumba et al 2005). Sansevistatin is one saponin derivative isolated from the plant reported to cause inhibition of cancer cell growth and also exhibit antimicrobial activity (Al-Fatimi et al 2007, Pettit et al 2005. The plant is also reported to be used for removal of toluene and ethylbenzene (Sriprapat et al 2014).…”
Section: Plants Usedmentioning
confidence: 99%